Design, preparation, and characterization of a polysaccharides-based hydrogel for applications in controlling nutrient release and water loss in agriculture - Parra Altamirano, Carla Lizbeth (2024)
Fertilizers applied to soil or directly to plants replenish nutrient levels, thus enhancing soil fertility and promoting healthy plant growth. However, conventional fertilization methods result in significant environmental pollution. This study presents the successful synthesis of hydrogels based on polysaccharides crosslinked with glutaraldehyde, loaded with calcium phosphate nanoparticles and urea, designed to address challenges related to soil fertilization and water retention. The newly developed controlled release systems were characterized using FTIR spectroscopy. Formulations B-R, A-R, and A demonstrated a notable water holding capacity of 78.50%, 72.32%, and 76.76%, respectively, resulting in soil water retention of 27.84%, 30.76%, and 33% over a 14-day testing period. Additionally, formulations B-R and A-R released 55% of urea and 75% of phosphate over 24 days, while formulation A released 76.69% of urea and 73.80% of phosphate within 6 days. These findings indicate that the newly developed hydrogels have significant potential to effectively address challenges related to fertilization and water retention, offering promising applications in sustainable agriculture.